Correlation of pruning time and fruiting part differentiation of sweet cherry cultivars - Vaszily, Barbara (Acta Agraria Debreceniensis, 2010)
There are several extended studies in sweet cherry production in Hungary and all over the world i.e. for creation and maintainence of smaller tree crown and high density orchards. The use of suitable dwarf rootstocks for this fruit species are very limited. On one hand, most of the draf rootstocks do not cause enough growth reduction and on the other hand these rootstocks are get old very quikcly and their fruits become small, and therefore, they not serve the requirements for intensification. In summary, there is a need for those rootstock which are vital, regeneration enhanching and delay ageing. Due to ensuring above features, Prunus mahaleb is still an obvious solution for intesive production. Increasing intensification can be obtained by use of modernisation of technological elements and suitable cultivar choice. According to this increasement of intensity through application of novel technological elements (timing, manner and severity of pruning) and selection of the proper cultivar is implement able. Important differences are experienced between sweet cherry cultivars in their growth attributes, light demand and dynamics of fall back in regenerative potencial of different aged wood parts. From this point knowledge of the abow detailed is very important in order to maintain rentability of already established plantations. Our work shows the formation of production part in9-year old plantation with spike spindle and free spindle crown forms depending on pruning timing (winter, summer) and determining of their various effects.